Interaction and Support from Haechan NCT Fans Through the Fanbase Instagram Account @Haechanoonaa - Amalia, Putri; Dian Lestari, Aghnia (International Journal Labs, 2026)
The development of social media has changed the patterns of interaction and the way fans express their support for K-Pop idols. Instagram fanbase accounts have become an important communication space in building relationships between fans and idols. This study discusses the forms of interaction and communication strategies developed by the Instagram fanbase account @haechanoonaa in interpreting fan support for Haechan NCT, with the aim of analyzing communication forms, support strategies, and the dynamics of fan identity formation. This study uses a descriptive qualitative method through the perspective of Herbert Blumer's symbolic interaction theory. Data collection techniques included online observation, in-depth interviews with fanbase administrators and account followers, and documentation of digital communication activities. The results of the study show that the @haechanoonaa account builds personal, interactive, and emotional communication through the use of visual symbols, informal language styles, and persuasive content. The interactions formed give rise to a sense of collective support, strengthen solidarity, and build a fan community identity. Thus, fanbase accounts serve as symbolic communication spaces that shape meaning through the exchange of symbols and build fan identity through engagement with idols on social media.